“Animal-Style Art,” and Special Finds at Iron Age Settlements in Southeastern Kazakhstan: Chronology, Trade, and Networks during the Iron Age - Claudia Chang; Sergei Sergievich Ivanov; Perry Alan Tourtellotte (Arts, 2023)
Two Iron Age settlements, Tuzusai and Taldy Bulak 2 (ca. 500 BC to 1 CE), located in southeastern Kazakhstan on the Talgar alluvial fan north of the Tian Shan range, have yielded a small collection of bone, antler/horn, bronze, and stone artifacts with an affinity to the nomadic art of the first millennium BC. Both settlements date within the period of late Saka culture. Two pieces have decorative ornamentations with zoomorphic imagery: a small carved fragment with carved images of a wing and an ear and a perforated bone disk with the carving of three birds’ heads. The other artifacts include objects associated with Saka weaponry or nomadic economy, such as two horn psalias (cheek pieces) and a bronze amulet. A carnelian bead will also be described as an imported object. These special finds were found on the occupation floors of mud brick houses and in the pit houses of settlements, not in grave or burial contexts. The objects were placed in a stratigraphic sequence in the settlement sites. The method for placing these objects within the chronological framework of “animal-style art” is through comparisons with similar objects found throughout Eurasia—a method used in Soviet and post-Soviet archaeology. The results show that the functional and stylistic elements of the six objects indicate that the Talgar settlements were part of a larger world-system of trade and communication along the early Silk Route(s).